A Review of Model Based Slicing and Test Case Generation - Grover, Venus; Kumar, Jitender (International Journal of Computer Sciences and Engineering, 2019)
To reduce error Software testing is important, upholding and overall software costs. To evaluate the feature or competency testing the software is an activity of system and determining that whether it meets required scenario. One way is program slicing to comfort, this method is to break down the large programs into smaller ones and further is model based slicing that split the large software architecture model into smaller models at the initial phase of SDLC (Software Development Life Cycle). To extract the sub model from a big model diagrams it is a completely new approach on the basis of slicing criteria. This planned procedure used the notion of model based slicing to segment the sequence diagram to extract the desired piece. An overview of Model based slicing is presented by this literature survey, including the different general methods and techniques used to compute slices. Our proposed test case generation technique can be used for integration and system testing accommodating the object message and condition information associated with the use case scenarios.